THE EFFORT OF INVESTIGATORS IN THE SETTLEMENT OF CHILD CASES TO PROVIDE JUSTICE FOR CHILDREN ACCORDING TO THE CHILD JUSTICE SYSTEM IN THE JURISDICTION OF THE POLICE OF THE PEKALONGAN CITY (CASE STUDY ON POLICE REPORT NUMBER: LP / B / 90 / VII / 2020 / Cen - Veni Nardianto (Indonesian Journal of Police Studies, 2022)
The process of conformity of children to a social group encourages children to do anything to be recognized and accepted. even though it is against positive law in Indonesia. In the general provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, the term is known as a child in conflict with the law. This paper aims to describe the competence of investigators from the PPA Satreskrim unit of the Pekalongan City Police and the investigators' efforts in resolving child cases in order to provide justice for children according to the juvenile justice system. The research in this final project uses the concept of a child in conflict with the law, the concept of premeditated murder and the concept of criminal investigation as well as competency theory and POAC management theory. This study uses a qualitative descriptive research method with a case study approach model. Data collection techniques using interview, observation and document studies. The final project research was carried out in the jurisdiction of the Pekalongan City Police. The results showed that the number of members of the PPA unit of the Pekalongan City Police Satreskrim did not match the list of personnel composition of Perkap No. 10 of 2007 concerning SOTK PPA Unit. Members of the PPA unit are also not designated as NCO for the education & protection unit for sure and among the members of the PPA unit there is only one person who has attended technical training in the investigation and protection of women & children. In the investigation process, the PPA unit of the Pekalongan City Police Satreskrim also had several shortcomings, namely there was no investigation plan product (Ren sik), the identity of the child perpetrator was spread in online news media, there was no special register book for children's cases and child detention was not placed in LPAS. Several findings during the study showed that the competence and process of investigating children in conflict with the law by the PPA unit of the Satreskrim Polres Pekalongan City was still not in accordance with the applicable laws and regulations. More intensive control and supervision is needed from the investigator's superiors to ensure that the unit's performance can be more optimal.